2011
DOI: 10.1007/s12160-011-9290-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mental Health Status and Health Behaviors of Survivors of Multiple Cancers: a National, Population-Based Study

Abstract: Background Little is known about the unique experience of adults with a history of multiple cancer diagnoses (i.e, survivors of multiple cancers). Purpose This research assessed the health status and health behaviors of survivors of multiple cancers. Methods The health status and health behaviors of 8734 survivors of multiple cancers, 47562 survivors of a single cancer, and 348229 non-cancer controls were compared using weighted data from the 2009 Behavioral Risk Factor Surveillance System. Results Survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
27
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 39 publications
10
27
2
Order By: Relevance
“…In addition, our finding regarding the lower risk for poor mental health among survivors with multiple cancers contrasts with recent population studies reporting worse physical and mental health outcomes for survivors of multiple cancers, compared to survivors with a single primary cancer (32, 33). This difference may be due to the specific outcomes examined (HRQOL vs mental distress, comorbidities, and disability) or the analytic strategy used for describing the effect.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, our finding regarding the lower risk for poor mental health among survivors with multiple cancers contrasts with recent population studies reporting worse physical and mental health outcomes for survivors of multiple cancers, compared to survivors with a single primary cancer (32, 33). This difference may be due to the specific outcomes examined (HRQOL vs mental distress, comorbidities, and disability) or the analytic strategy used for describing the effect.…”
Section: Discussioncontrasting
confidence: 99%
“…This difference may be due to the specific outcomes examined (HRQOL vs mental distress, comorbidities, and disability) or the analytic strategy used for describing the effect. Burris & Andrykowski (32, 33) treated multiple cancers as a distinct group, comparing them to both single primary survivors and no-cancer controls. In contrast, we used single/multiple cancers as a covariate in multiple regression models that also controlled for site of most recent cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Study limitations are acknowledged. While the survey response rate was lower than expected and could have introduced bias, we were adequately powered to conduct analyses, our participants were similar to those in previously recruited national MPC samples (ie, age, gender, and partner status), and study participants were similar to all potentially eligible nonparticipants on all examined characteristics. We also recruited a sample with high variability in educational attainment, which was identified as a predictor of self‐management behaviors.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, second (or more) primary cancer diagnoses represent about 16% of all incident cancer diagnoses in the United States 4. Despite this large and growing number of survivors of multiple cancers, only 2 studies have examined the current physical and mental health status of these individuals 5, 6. In a study limited to Hawaii residents, survivors of multiple primary cancer diagnoses reported poorer global quality of life, less vitality, greater cancer‐specific distress, and poorer existential well‐being than matched survivors of a single primary cancer diagnosis 6.…”
Section: Introductionmentioning
confidence: 99%